Floristic diversity and management of fodder resources of the natural pastures of the Savanna Highlands of Western Cameroon - Baudoin, Wouokoue Taffo Junior; Louise, Avana Tientcheu Marie; Yougouda, Hamawa; Francois, Nguetsop Victor; Roger, Tsobou; Jonathan, Ngnignindiwou Mouncharou (Journal of Experimental Sciences, 2020)
Sustainable management of pastoral resources requires knowledge in terms of floristic diversity and productivity of the rangelands. The objective of the present study carried out in the Bamboutos Mountains was to assess the floristic diversity and carrying capacity of the natural pastures. Floristic inventory was done using the method of quadrat point aligned in 15 plots of 400 m². Aerial phytomass of herbaceous plants was measured by the full harvest method. A total of 74 species, including 09 woody plants belonging to 56 genera and 20 families were recorded. The number of taxa recorded in the plots varied from 11 to 36 species. Imperata cylindrica with a specific contribution of presence of 17.45% was the most abundant species in the rangeland. The species-richest families were Poaceae, Fabaceae, Asteraceae and Cyperaceae. The calculated pastoral value of the pasture was 56.21%. These pastures were dominated by phanerophytes (29.72%) and therophytes (24.32%). The forage productivity of the grazed area, estimated based on the regrowth biomass was 6498.57 kg DM/ha while the carrying capacity of the rangeland was 2.31 TLU/ha. These results showed that the fodder potential of the Bamboutos Mountains is enough diversified but remains under exploited.